Foreign body - Cook, Robin, 1940- (New York : G.P. Putnam's Sons, 2008)
A series of unexplained deaths in foreign hospitals sends Jennifer Hernandez, an idealistic UCLA medical student, on a desperate search for answers about her grandmother's sudden death. With the discovery of other unexplained deaths followed by hasty cremations, Jennifer reaches out to her mentor, New York City medical examiner Dr. Laurie Montgomery, who has her own deep connection to Jennifer's grandmother.
Keywords: Women medical students -- Fiction; Grandmothers -- Death -- Fiction; Hospitals -- India -- Fiction; Medical novels